Atomistic simulations of defect accumulation and evolution in heavily irradiated titanium for nuclear-powered spacecraft - Hai Huang; Xiaoting Yuan; Longjingrui Ma; Jiwei Lin; Guopeng Zhang; Bin Cai (Nuclear Engineering and Technology, 2023)
Titanium alloys are expected to become one of the candidate materials for nuclear-powered spacecraft due to their excellent overall performance. Nevertheless, atomistic mechanisms of the defect accumulation and evolution of the materials due to long-term exposure to irradiation remain scarcely understood by far. Here we investigate the heavy irradiation damage in α-titanium with a dose as high as 4.0 canonical displacements per atom (cDPA) using atomistic simulations of Frenkel pair accumulation. Results show that the content of surviving defects increases sharply before 0.04 cDPA and then decreases slowly to stabilize, exhibiting a strong correlation with the system energy. Under the current simulation conditions, the defect clustering fraction may be not directly dependent on the irradiation dose. Compared to vacancies, interstitials are more likely to form clusters, which may further cause the formation of 1/3<1¯210> interstitial-type dislocation loops extended along the (¯1010) plane. This study provides an important insight into the understanding of the irradiation damage behaviors for titanium.